2022
DOI: 10.3389/fphys.2022.1023453
|View full text |Cite
|
Sign up to set email alerts
|

Modified Baihu decoction therapeutically remodels gut microbiota to inhibit acute gouty arthritis

Abstract: Background: Acute gouty arthritis (AGA) is the most common first symptom of gout, and the development of gout as a metabolic and immune inflammatory disease is also correlated with the gut microbiota. However, the mechanism of the effect of changes in the gut microbiota on AGA remains unclear. The intestinal flora can not only affect purine metabolism or regulate inflammation, but also influence the therapeutic effect of drugs on AGA. The aim of this study was to investigate the exact mechanism of modified Bai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Rats in the Normal group were injected with NS, and in other groups were injected with MSU. The previous studies ( Fischer et al, 2018 ; Zhao J. et al, 2022 ; Wang X. et al, 2022 ; Zhao L. et al, 2022 ) have demonstrated that 8 h after the MSU injection is the key point for AGA Model. We observed the swelling of rat knees, with few changes in the Normal control group, while it had obvious redness and swelling in the Model group ( Figure 6A ), suggesting that the AGA model was established successfully by MSU injection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rats in the Normal group were injected with NS, and in other groups were injected with MSU. The previous studies ( Fischer et al, 2018 ; Zhao J. et al, 2022 ; Wang X. et al, 2022 ; Zhao L. et al, 2022 ) have demonstrated that 8 h after the MSU injection is the key point for AGA Model. We observed the swelling of rat knees, with few changes in the Normal control group, while it had obvious redness and swelling in the Model group ( Figure 6A ), suggesting that the AGA model was established successfully by MSU injection.…”
Section: Resultsmentioning
confidence: 99%
“…Their intricate composition, multifaceted therapeutic targets, and intricate treatment modalities present formidable challenges to the comprehensive elucidation of their underlying mechanisms. In recent times, network pharmacology has risen to prominence as a favored methodology for dissecting the intricate mechanisms of action inherent to complex Traditional Chinese Medicine (TCM) formulations ( Wang et al, 2020b ; Liu et al, 2023 ). OB and DL values are based on general rules and assumptions about compound properties, such as molecular weight, lipophilicity, and solubility.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the Chinese Formula Wuling san ( Yang et al, 2015 ), Cheqianzi decoction ( Meng et al, 2023 ), Baihu decoction ( Wang et al, 2022b ), Sanhuang- Xiexin decoction ( Wu et al, 2019 ) and Shizhi fang ( Zhou et al, 2023 ) have exhibited significant effects in gout prevention by operating through pathways linked to the inhibition of the NLRP3 signaling cascade and the mitigation of renal damage.…”
Section: Signal Pathways Of Tcm Modulating Gout Pathological Progressionmentioning
confidence: 99%
“…Another study discovered that TRQI exhibited favorable antipyretic and wake-promoting effects, while also mitigating the incidence of complications ( Yu et al, 2017 ). XNJI, another derivative CPM of the herbal prescription Angong Niuhuang, has been extensively employed as an emergency intervention in cases of acute cerebral injury or infarction and stroke ( An et al, 2022 ; Wang et al, 2022b ). A study indicated that XNJI has the potential to mitigate cerebral ischemia/reperfusion injury through the inhibition of the inflammatory response mediated by SIRT1( Zhang et al, 2020 ).…”
Section: Chinese Patent Medicines Of Tcm Against Hsmentioning
confidence: 99%